Phenomena of Corruption as A Social Pathology: A Review on Legal Sociology - Muhammad Rahjay Pelengkahu; Fajri M Kasim (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2023)
This research examines the factual issues of eradicating and legal enforcement of corruption in Indonesia. In addition, the phenomenon of corruption as a social sickness is evaluated from the perspective of legal sociology research. Utilizing a descriptive-analytical research approach, literature studies are conducted to collect a variety of trustworthy resources and information. The study's findings indicate that the problem of eradicating and enforcing anti-corruption laws in Indonesia has become a cycle of corruption that will not end unless the state undertakes supremacy-reform initiatives in three areas: socio-cultural, legal instruments, and institutional-structural-functional. Corruption has become societal cancer that affects the development of legal culture in society. Corruption is viewed as a structural functionalism framework. Deviant conduct of officials v from a breach of the social structure's functioning.